Monitoring of polycyclic aromatic hydrocarbons in transplanted mussels (Mytilus galloprovincialis) and sediments in the coastal region of Nemrut Bay (Eastern Aegean Sea). (August 2020) - Kucuksezgin, Filiz; Gonul, L. Tolga; Pazi, Idil; Ubay, Bahar; Guclusoy, Harun
Abstract: Polycyclic aromatic hydrocarbons (PAHs) were determined in the coastal region of Nemrut Bay, Eastern Aegean. Sediment and caged mussels were evaluated for sixteen PAHs. High contamination was observed in the sediment sampling sites next to the petrochemical refinery. Low molecular weight PAH levels were dominant in the sediments and the ratio LMW/HMW were higher than one, indicating petrogenic origin pollution. The m-ERM-q values of the sediments were classified as high-priority sites near the refinery while other sites were categorized as medium-low sites. 4-ring PAHs were found to be dominant in the mussels. PAHs were originated from petroleum and mixed sources (petrogenic, pyrogenic) both two transplantation experiments. The assessment of human health risk based on the Carcinogenic `Toxic Equivalents suggested that the mussels have high capability to give rise to carcinogenic risks. PAH levels in the mussels were above the Recommended Total Carcinogenic PAH limits set by the European Union.